Application of Cybernetetic Learning Theory Using Visual Illustration Media to Develop Students' English Speaking Skills - Sriwati Sriwati; Ruhanda Ruhanda; Erwin Yulianto (Fakultas Keguruan dan Ilmu Pendidikan Universitas Pakuan, 2020)
The ability to speak English is a must to survive in global competition. As education people always try and want to explore to improve the quality of graduates who are better with a variety of methods, but the results are still not satisfactory as expected. Various attempts to improve English learning outcomes have been carried out through suitable and fun learning models using in-service and on-service training systems, but after completing the training many teachers returned to the old teaching method (teacher centered). Communicative approach methods / approaches have not been implemented so that the results achieved have not been improved. Of the four English language skills, the lowest score is speaking skills. The main cause is the low student interest in learning and the use of media that is less interesting, coupled with teaching and learning activities in the classroom that are boring. Seeing this kind of teacher creativity is needed, for example by conducting teaching and learning activities based on visual illustration media according to the tastes of the child but so that it can meet the demands of the curriculum and keep abreast of technological developments. The research method used is to use the concept of Action Research Class which consists of 2 cycles, where each cycle consists of several stages, namely planning, action implementation, observation and evaluation and reflection. Classroom action research on improving speaking English by applying cybernetic learning theory and visual illustration media carried out over two cycles is able to be an alternative learning reference for teachers and students who are fun.